Initial growth of tree species grown on salinized soil with conditioners - Araujo, Josinaldo Lopes; Oliveira, Saul Ramos de; Sousa, Flaubert Queiroga de; Silva, Alexandre Paiva da (Comunicata Scientiae, 2018)
The excess of salts and sodium is one of the factors that contribute most to the soil chemical degradation. Recovery of these soils requires the establishment of techniques using soil conditioners and more tolerant species. The present study aimed to evaluate the effect of soil conditioners on the recovery of a saline - sodic soil and on the growth and physiological responses of tree species. Two experiments were carried out in a greenhouse, both using a completely randomized design. In the first experiment, five treatments were evaluated for soil correction: saline soil with no correction, saline soil + calcium sulfate, saline soil+ sulfur, saline soil + O.M. (organic matter) and non saline soil. The second experiment, consisted of a 4x5 factorial arrangement, with four trees species (Amburana cearensis, Caesalpinia ferrea, Cnidosculus philacanthus and Moringa oleifera) and the five treatments described in the first experiment, with three repetitions. Bovine manure, elemental sulfur and calcium sulfate decrease the salinity and sodicity of saline-sodic soils, especially the latter two, which attenuate the negative effects of salinity and sodicity on the photosynthetic rate of C. philacanthus, M. oleifera and C. ferrea, favoring the growth and dry matter production of C. ferrea and M. oleifera.